Doing research on the internet - Wilson, Nancy Rabuck; Rodriguez, Carlo; Russell, Anne; Greene, Ronald; Educational Video Network (Huntsville, TX: Educational Video Network, 1998)
Demonstrates the power of the Internet as a research tool
Videography, Joe Abercrombie
Narrated by Jude L. Routh
Keywords: Internet (Computer network); Internet (Computer network) in education; Internet in education